Concentrations and cycling of DMS, DMSP, and DMSO in coastal and offshore waters of the Subarctic Pacific during summer, 2010‐2011. Issue 4 (24th April 2017) - Asher, Elizabeth; Dacey, John W.; Ianson, Debby; Peña, Angelica; Tortell, Philippe D.
Abstract: Concentrations of dimethylsulfide (DMS), measured in the Subarctic Pacific during summer 2010 and 2011, ranged from ∼1 to 40 nM, while dissolved dimethylsulfoxide (DMSO) concentrations (range 13‐23 nM) exceeded those of dissolved dimethyl sulfoniopropionate (DMSP) (range 1.3–8.8 nM). Particulate DMSP dominated the reduced sulfur pool, reaching maximum concentrations of 100 nM. Coastal and off shore waters exhibited similar overall DMS concentration ranges, but sea‐air DMS fluxes were lower in the oceanic waters due to lower wind speeds. Surface DMS concentrations showed statistically significant correlations with various hydrographic variables including the upwelling intensity (r 2 = 0.52, p < 0.001) and the Chlorophyll a /mixed layer depth ratio (r 2 = 0.52, p < 0.001), but these relationships provided little predictive power at small scales. Stable isotope tracer experiments indicated that the DMSP cleavage pathway always exceeded the DMSO reduction pathway as a DMS source, leading to at least 85% more DMS production in each experiment. Gross DMS production rates were positively correlated with the upwelling intensity, while net rates of DMS production were significantly correlated to surface water DMS concentrations. This latter result suggests that our measurements captured dominant processes driving surface DMS accumulation across a coastal‐oceanic gradient. Plain Language Summary: The trace gas dimethyl sulfide is a precursor for natural, sulfur‐based aerosols that influence climate, an important compound in marine microbial communities, and an olfactory foraging cue for seabirds. This article discusses data from two surveys of dimethyl sulfide in 2010 and 2011 in the Subarctic Northeast Pacific ocean. The surveys consisted of extensive concentration measurements across this region and in specific locations, novel rate measurements of the biological and chemical production and removal of this gas. We found that dimethyl sulfide concentrations may be predicted from the measured rates of its production and consumption. In coastal waters, dimethyl sulfide concentrations appear related to the supersaturation of biological oxygen in surface waters. Key Points: DMS heterogeneity and turnover rate increased from oceanic waters shoreward DMS concentrations were correlated with biological oxygen accumulation and upwelling intensity in coastal waters DMS turnover rates are significantly correlated with observed DMS concentrations